Takabur dalam Perspektif Hadis - Amar Firdaus; Muhammad Alif (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2024)
Takabur is a behavior that refers to a person's arrogant, conceited, or boastful attitude towards other people. In Islam, takabur is referred to as one of the eight major sins that must be avoided, because it deviates or violates the principle of humility and the recognition that all humans are equal before Allah SWT. This research aims to identify and understand the factors that influence the development of takabur behavior based on hadith. The discussion in explains immoral behavior, its impacts, and how to avoid it referring to the hadith of the Prophet SAW. The method used in this research is contemporary hadith thematics. This research concludes that it is important for every individual to avoid takabbur and strive to develop an attitude of humility, humility, and simplicity through the application of hadith.